Analytical Study of Vyadhi Lakshan W.S.R. to Pandu Roga (International Journal of Ayurveda and Pharma Research, 2022)
Following the intake of various causative factors, three fundamental alterations happen within human body - vitiation of Dosha (Dosha Prakopana), affliction of Dhatus by vitiated Doshas (Dhatu Pradushana) and impairment of channels (Kha Vaigunya). Localization of vitiated Doshas within channels depends on the site of Kha Vaigunya which ultimately leads to interaction between vitiated Dosha and Dhatus - known as Dosha Dushya Sammurchhana . Dosha Dushya Sammurchhana takes place following two principles of amalgamation - Prakriti Sama Samavaya and Vikriti Vishama Samavaya. As consequence of this amalgamation, several signs and symptoms do appear in body depending on the involved Dosha, Dhatu, state of Agni, type of Srota & Srotadusti and various other factors. Clinical features of any disease can be classified in to two category - those which appears before the onset of actual disease are known as Purva Rupa or prodromal features and when these features become more prominent in the mature state of disease, they are called Rupa / Lakshana or main clinical features. The mechanism behind appearance of every sign and symptom in the course of illness can be explained on the basis of several factors like involved Dosha, Dhatus, Agni, Srota, Oja and various other factors depending on the principle of Karya Karana Vada. Thus these clinical features of any disease which are mentioned in different classical texts should not be regarded as just mere scholarly inference, rather each and every symptoms can be explained methodically applying the principles of Ayurveda. For this purpose, example of a common disease in form of Pandu Roga has been taken in this article and explanation has been given about the possible mechanism of appearance of various prodromal features and principal features of this disease.